Utility of low-profile visualized intraluminal support (LVIS™) stent for treatment of acutely ruptured bifurcation aneurysms: A single-center study - Liu, Changya; Guo, Kaikai; Wu, Xinxin; Wu, Linguangjin; Cai, Yike; Hu, Xuebin; Fang, BangJiang (Frontiers in Neurology, 2023)
Objective Stent-assisted coiling has been increasingly used in the treatment of intracranial aneurysms. However, its application in ruptured bifurcation aneurysms remains controversial and challenging. This study aimed to present the safety and feasibility of low-profile visualized intraluminal support (LVIS™, LVIS, and LVIS Jr.) stent for acutely ruptured bifurcation aneurysms. Methods A total of 41 patients with acutely ruptured intracranial aneurysms arising at the bifurcation were treated with LVIS™ stent-assisted coiling in our hospital between January 2017 and December 2021. The clinical data and angiographic results of the patients were analyzed. Results Among these patients, all stents were successfully implanted. According to the immediate angiographic results, 29 aneurysms (70.7%) were completely occluded. Intraoperative thrombosis and hemorrhage occurred in two and one cases, respectively. No post-operative thrombosis or rebleeding events were observed. The clinical follow-up of all patients revealed that 38 (92.7%) cases had favorable outcomes (modified Rankin scale: 0–2). The angiographic results available for the 36 patients during the follow-up period revealed complete occlusion was achieved in 30 patients (83.3%) and residual neck in six patients. Conclusion The LVIS™ stent-assistant coiling is a safe and feasible option for acutely ruptured bifurcation aneurysms. Further studies with a prospective design, a larger sample size, and long-term follow-up are needed to validate these findings.